Legacy of war - Smith, Wilbur A. (Smith, Wilbur A. Courtney series., 2021)
The war is over, Hitler is dead, and yet his evil legacy lives on. Saffron Courtney and her beloved husband Gerhard only just survived the brutal conflict, but Gerhard's Nazi-supporting brother, Konrad, is still free and determined to regain power. As a dangerous game of cat-and-mouse develops, a plot against the couple begins to stir. One that will have ramifications throughout Europe. Further afield in Kenya, the last outcrop of the colonial empire is feeling the stirrings of rebellion. As the situation becomes violent and the Courtney family home is under threat, Leon Courtney finds himself caught between two powerful sides and a battle for the freedom of a country.